2019
DOI: 10.1007/s13167-019-00165-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between protocols and publications of case-control studies: analysis of potential causes of non-reproducibility and recommendations for enhancing the quality of personalization in healthcare

Abstract: Background Selective reporting of results in published case-control studies has been widely suspected, but little comprehensive information on selective reporting is available with regard to case-control studies. We aimed to evaluate the concordance of findings between publications and the protocols of case-control studies and to assess the level of selective reporting of results in case-control studies. Methods The databases of Embase, Medline, Scopus, and Web of Science were searched to identify case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…However, no protocols were identified in the systematic search and none of the included studies referred to a published protocol, implying that this is not currently practiced within the field of gut microbiota in neurodevelopmental disorder. A related bias is the outcome reporting bias, describing the tendency to only report outcomes with a result 326 . Indeed, several studies were included that did not state whether they observed variations in alphadiversity as evident in table 2.…”
Section: Limitationsmentioning
confidence: 99%
“…However, no protocols were identified in the systematic search and none of the included studies referred to a published protocol, implying that this is not currently practiced within the field of gut microbiota in neurodevelopmental disorder. A related bias is the outcome reporting bias, describing the tendency to only report outcomes with a result 326 . Indeed, several studies were included that did not state whether they observed variations in alphadiversity as evident in table 2.…”
Section: Limitationsmentioning
confidence: 99%